Viral Retinitis with Co-Infection Cytomegalovirus and Varicella Zoster - Dhaivat Shah; Ravin Punamia; Bennet Chacko Mathew; Rahul Singh; Milind Rokade (Delhi Journal of Ophthalmology)
Combined infection with cytomegalovirus (CMV) and varicella-zoster virus (VZV) is a rare entity, especially in an immunocompetent person. Almost all cases with co-infection are either immunocompromised or on immunosuppressant. Here, we present to you one such case of a 31-year-old male who presented with complaints of sudden diminution of vision in his right eye after a bout of fever. After a battery of investigations, the patient was found to have raised blood titers of CMV and VZV. The patient was put on oral antivirals and steroids, followed by a vitrectomy, which yielded a good outcome.